-3(3y-4)-y=-4(y-4)

Simple and best practice solution for -3(3y-4)-y=-4(y-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3y-4)-y=-4(y-4) equation:



-3(3y-4)-y=-4(y-4)
We move all terms to the left:
-3(3y-4)-y-(-4(y-4))=0
We add all the numbers together, and all the variables
-1y-3(3y-4)-(-4(y-4))=0
We multiply parentheses
-1y-9y-(-4(y-4))+12=0
We calculate terms in parentheses: -(-4(y-4)), so:
-4(y-4)
We multiply parentheses
-4y+16
Back to the equation:
-(-4y+16)
We add all the numbers together, and all the variables
-10y-(-4y+16)+12=0
We get rid of parentheses
-10y+4y-16+12=0
We add all the numbers together, and all the variables
-6y-4=0
We move all terms containing y to the left, all other terms to the right
-6y=4
y=4/-6
y=-2/3

See similar equations:

| 5b=5b | | -4/x+1=5/3x+1 | | -27+-3x=33 | | 33=1/2h(2+9) | | 15+y=17 | | 1x-16=x+2 | | i+0=9 | | f(0)=4(0)-5 | | c+.25=5 | | 6(4+z)=2z | | 14+-28=21t-6-8 | | 8x-6x+174=8x+96 | | 19x–5=2 | | 7y+6=6y-2+6y | | 30x-8=21 | | 30x–8=21 | | 18=a×2 | | 6+12x=6(x-9) | | 9/x+6=2/3x | | 4(5+-0.5y)+2y=20 | | -5(3y-10)-y=-2(y-3) | | 13/4=1/2+w | | 22x+45=15 | | 3x-5(x-4)=-2x+3-8 | | 5x+7/x-1=3x+2 | | 9y+6=3y-2+8y | | 2x+3(x+2)=x+10+2x | | 33+15+x+20=21 | | 38=(2-3x)4 | | -8a^2-10a+3=0 | | 10/8+h=3-2 | | 125=3300x+65 |

Equations solver categories